Importance of Toxin A, Toxin B, and CDT in virulence of an epidemic Clostridium difficile strain - Kuehne, Sarah A.; Collery, Mark M.; Kelly, Michelle L.; Cartman, Stephen T.; Cockayne, Alan; Minton, Nigel P. (Oxford University Press, 2013)
Clostridium difficile infection is the main cause of healthcare-acquired diarrhea in the developed world. In addition to the main virulence factors toxin A and B, epidemic, PCR Ribotype 027 strains, such as R20291, produce a third toxin, CDT. To develop effective medical countermeasures, it is important to understand the importance of each toxin. Accordingly, we created all possible combinations of isogenic toxin mutants of R20291 and assessed their virulence. We demonstrated that either toxin A or toxin B alone can cause fulminant disease in the hamster infection model and present tantalizing data that C. difficile toxin may also contribute to virulence.